Selective Antisite Defect Formation in WS2 Monolayers via Reactive Growth on Dilute W‐Au Alloy Substrates (Adv. Mater. 3/2022). Issue 3 (21st January 2022) - Wang, Kai; Zhang, Lizhi; Nguyen, Giang D.; Sang, Xiahan; Liu, Chenze; Yu, Yiling; Ko, Wonhee; Unocic, Raymond R.; Puretzky, Alexander A.; Rouleau, Christopher M.; Geohegan, David B.; Fu, Lei; et al.
Abstract : 2D Materials In article number 2106674, Kai Xiao and co‐workers develop a nonequilibrium chemical vapor deposition approach for selective formation of antisite defects in atomically thin 2D tungsten sulfide monolayer crystals by regulating the diffusion of tungsten into gold substrates. This work demonstrates a novel strategy for the selective formation of defects in 2D materials by tuning their formation energy during synthesis via choice of substrate and alloy design.